Relevansi Dan Urgensi Aplikasi Metodologi Kritik Hadis Dalam Penelitian Al-Sirah Al-Nabawiyyah - Fuad Hilmi; Sholihin Firman; Rizal Samsul Mutaqin (Diroyah : Jurnal Studi Ilmu Hadis, 2022)
The position of al-sirah al-nabawiyah is very important, because it portrays the history of the early generations of Islam (the Prophet and the Companions), which is actually the face of Islamic history as a whole. This paper aims to describe al-sirah al-nabawiyyah, both normatively and historically, in order to find the relevance and urgency of applying the Hadith criticism methodology in his research. The method used in this research is descriptive-qualitative. The source of the data is literature with the data collection technique used is document study. The data have been collected and analyzed use you-kan-critical content analysis methods(contentanalysis).The results of this study indicate that hadith and srah are basically the same, both in linguistic and historical perspectives, only their orientation is different; Hadith as an instrument of Islamic legislation (creed and sharia) and srah as a historical construction of the Prophet. The construction of most of the narrations of al-srah al-nabawiyyah in its primary sources is no different from the hadith; begins with a chain of chains. Thus, applying the hadith criticism method in al-srah al-nabawiyyah research is not only appropriate (relevant), but very important (urgent).